Forced Degradation and Stability Analysis of a Fixed-Dose Combination for Tuberculosis in HIV Patients - Rathinasamy M, Rathinasamy M; Palaniappan, Senthilkumar (Journal of Neonatal Surgery, 2025)
Tuberculosis (TB) remains a major health challenge, particularly among HIV-infected individuals, due to their compromised immune systems. This study aimed to develop and evaluate a Fixed-Dose Combination (FDC) of Sulfamethoxazole, Trimethoprim, Isoniazid, and Pyridoxine Hydrochloride for the treatment of secondary TB in HIV patients. The study involved forced degradation, stability analysis, and validation of an RP-HPLC method for simultaneous quantification of the active pharmaceutical ingredients (APIs). The forced degradation study revealed that the FDC formulation degraded significantly in acidic (0.1N HCl) and oxidative (3% H₂O₂) conditions, while it remained stable under thermal (70°C dry heat) and photolytic (UV 254 nm) conditions. The stability study, conducted under accelerated (40°C, 75% RH) and intermediate (30°C, 75% RH) conditions over 24 months, demonstrated that the FDC maintained physical integrity, dissolution efficiency (NLT 75% within 60 minutes), and assay compliance (90-110% of labeled claims). The HPLC method validation confirmed high accuracy, precision, linearity, specificity, and robustness in detecting all four drugs simultaneously. These findings suggest that this FDC formulation is stable, bioavailable, and suitable for clinical use in TB-HIV co-infected patients. Further clinical trials are recommended to validate therapeutic efficacy in human subjects